The Bali Convention: flexibility of targets and instruments inevitable - Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
The Kyoto Protocol is one first important step towards a global greenhouse gas emissions reduction strategy. In order to avoid irreversible climate changes and huge economic damage, not just some but all of the responsible nations should agree on a joint proposal to reduce emissions. Sharing the burden fairly would mean that those nations with high emissions per capita should reduce them more than countries with low emissions per capita. However, a fair burden sharing should also take into account early action and economic and social conditions. Most of the countries, especially those with high economic growth, fear large economic losses if emissions reduction targets are very high. Especially fast-growing nations such as China and India suspect negative consequences if climate policy takes a dominant role. The post-Kyoto negotiations can only be successful if flexibility of targets and instruments is considered. The next UN climate conference, at the end of 2007 in Bali, is an important starting point for a so-called Bali Convention. This convention should take into account different emissions reduction options and flexible emissions reduction targets. Germany's Chancellor Merkel supports a world per capita emissions target; Europe should find soon a fair burden sharing between the EU member states and start negotiations with 30 % emissions reduction in order to make clear how serious EU is to reduce emissions. The APEC nations favour an energy intensity reduction target. The emissions intensity of a nation can be reduced if CO2-free technologies are widely applied. Nations with a large share of CO2 emissions resulting from high fossil-fuel usage or high methane emissions from energy production or agriculture usually favour flexible indexed targets. The Bali Convention should define such flexible targets to take into account national conditions and visions. It is most important that countries agree on binding targets, either concrete emissions reduction targets or indexed targets such as emissions intensity or per capita emissions. The key to success is flexibility of targets and instruments.
Keywords: 330; Klimaschutz; Immissionsschutz; Flexibilität; Umweltabkommen; Welt